Investigating Prevalence of Risk Factors of Hepatitis ‘B’ Among Staff and Students of Public Tertiary Institutions in Nigeria: Implication for Health Security in Education - Jesse, Victor Shabminu; Kukwi, Isaac; Osu, Tanimu; Aminu, Danladi Abubakar; Abdullateef, Alade Oluyemo (NIU Journal of Educational Research; Vol 10 No 1 (2024): NIU Journal of Educational Research, Vol. 10 No. 1, June 2024DO - 10.58709/niujed.v10i1.1933, 2024)
Just as academic staff of any tertiary institution are employed to enhance learning through instructions and other services that promotes institutional mission, so also, students are admitted in school to acquire knowledge, and to be given the best possible chances of achieving good and quality education but not to return home with a transmissible disease like Hepatitis ‘B’ Virus (HBV). The purpose of this study was to investigate the prevalence of risk factors of HBV among academic staff and students of tertiary institutions along gender lines, as implication for health security to education. A cross-sectional descriptive study was carried out in three selected public tertiary institutions within Niger State. The study adopted 90 academic staff (51 males and 39 females), and 348 students (156 males and 192 females) selected randomly from the three institutions. A self-developed questionnaire titled Questionnaire for Assessment of Prevalence of Risk-Factors of Hepatitis B Virus (SQ-APRF-HBV) for both academic staff and students was used to collect data. Data collected were analyzed using mean, standard deviations, and t-test at 0.05 level of significant difference. The findings of the study revealed that there is statistical significant difference between the male and female academic staff in sexual health and behavior and in blood transfusion related activities. This is evident as results showed 17.00 for sexual health and behavior, and 3.86 in blood transfusion related activities, which are greater than the critical value of 1.990. For sexual health and behavior, sharing of supposed personal items, use of unsterilized items, and blood transfusion related activities among tertiary students showed -3.59, -19.62, -32.62 and 0.89 respectively, all less than the critical value of 1.960. Mandatory HBV test for staff and students, among others were recommended. Keywords: Hepatitis ‘B’, Risk Factors, Academic Staff, Students, Tertiary Institutions, Health Security and Transmission